ANALISA DEFECT PERFORMANCE PRODUK MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL - Dito Samudera Sucahyo; Joumil Aidil Saifuddin (JOURNAL SAINS STUDENT RESEARCH, 2024)
. Research on broadplates and screws that are useful to help maintain the position of broken bones to remain in a normal position is one of the medical devices that require close supervision in the manufacturing process. Determining what factors cause damage or defects in BroadPlate DCP products is the purpose of this study. The method used in this study is statistical quality control. After the application of the SQC method, it is known that 3 types of defects have an influence on each defect such as inappropriate material, no Re-Check, less strict Quality Control, less preparation, miscalculation, placement errors, machine maintenance, noisy conditions.